A survival kit for the secondary school art teacher - Hume, Helen D., 1933- (Center for Applied Research in Education, 1990)
This book contains: Two-Dimensional Design; Three-Dimentional Design; Drawing; Painting; Ceramics; Sculpture; Crafts; Printmaking; Photography; and Basic Survival Strategies for Your Art Program.